2016
DOI: 10.1111/dme.13159
|View full text |Cite
|
Sign up to set email alerts
|

Patients with KCNJ11‐related diabetes frequently have neuropsychological impairments compared with sibling controls

Abstract: Aims KCNJ11-related diabetes is the most common form of permanent neonatal diabetes and has been associated with a spectrum of neurodevelopmental problems. We compared neurodevelopmental outcomes in subjects with KCNJ11 mutations and their sibling controls. Methods Through our Monogenic Diabetes Registry (http://monogenicdiabetes.uchicago.edu/), we evaluated 23 subjects with KCNJ11 mutations with (n=9) and without (n=14) global developmental delay successfully treated with sulfonylurea and 20 healthy sibling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 28 publications
(34 reference statements)
1
47
0
Order By: Relevance
“…Our findings using a different battery of tests are consistent with the study by Carmody et al . , where only 2/9 children with global developmental delay were able to complete any neuropsychological tests, and scores in tests they did complete were the lowest of the group. In those children without global developmental delay, compared with unaffected sibling controls, Carmody et al .…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Our findings using a different battery of tests are consistent with the study by Carmody et al . , where only 2/9 children with global developmental delay were able to complete any neuropsychological tests, and scores in tests they did complete were the lowest of the group. In those children without global developmental delay, compared with unaffected sibling controls, Carmody et al .…”
mentioning
confidence: 95%
“…We support the findings of Carmody et al . , who offered new insights into the neurological phenotype of people with KCNJ11 neonatal diabetes. Neurological features result from the K ATP channel affected by these mutations being expressed in the brain as well as the pancreas .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although certain KATP mutations have consistently been reported to be associated with significant developmental delay and/or seizures termed DEND (developmental delay, epilepsy, neonatal diabetes), it has not been clear whether those without obvious developmental delay may in fact have more mild neurodevelopmental and/or behavioral challenges. A study of KCNJ11 patients ( n =23) and their unaffected siblings ( n = 20) revealed that even patients with more mild KCNJ11 mutations (“without global developmental delay”) had significant differences in performance on standardized tests compared to their siblings [16•]. These differences were present in areas such as IQ, academic achievement, and executive function, while those patients with global developmental delay also exhibited differences in social awareness and behavior.…”
Section: Kcnj11/abcc8: Congenital Diabetes Due To Activating Mutationmentioning
confidence: 99%
“…The first paper describes how children with KCNJ11 mutations, with and without global developmental delay, had significant differences on a range of assessments including IQ, measures of academic achievement and executive function compared with their unaffected siblings. In those with global delay, there were differences in behavioural symptoms, which had effects across all aspects of daily living [7]. Psychiatric features may also occur as described in the paper by Bowman et al [8], who systematically characterize the types of psychiatric disorders in children with KCNJ11 mutations and their effects.…”
mentioning
confidence: 94%